2012
DOI: 10.3390/ijms13032877
|View full text |Cite
|
Sign up to set email alerts
|

An Oligodeoxynucleotide That Induces Differentiation of Bone Marrow Mesenchymal Stem Cells to Osteoblasts in Vitro and Reduces Alveolar Bone Loss in Rats with Periodontitis

Abstract: To investigate the effect of oligodeoxynucleotides (ODNs) on the differentiation of rat bone marrow mesenchymal stem cells (BMSCs) to osteoblasts, in order to find a candidate ODN with potential for the treatment of periodontitis, a series of ODNs were designed and selected to test their effect on the promotion of the differentiation of BMSCs to osteoblasts in vitro and on the repair of periodontal tissue in rats with periodontitis. It was found that MT01, one of the ODNs with the sequences of human mitochondr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 38 publications
0
24
0
Order By: Relevance
“…Our previous studies have found that ODN MT01 could regulate the balance of bone formation and resorption, and that it therefore has a great potential in the rebuilding of alveolar bone. [5][6][7] Here we applied PEN as a carrier for MT01 delivery with the aim to enhance its cellular uptake capability and its stability. Different types of PEI are regarded as the most effective nonviral gene vectors due to their ability to reduce the negative charge of DNA and to partially condense its normally large hydrodynamic volume and the ability to escape from lysosomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous studies have found that ODN MT01 could regulate the balance of bone formation and resorption, and that it therefore has a great potential in the rebuilding of alveolar bone. [5][6][7] Here we applied PEN as a carrier for MT01 delivery with the aim to enhance its cellular uptake capability and its stability. Different types of PEI are regarded as the most effective nonviral gene vectors due to their ability to reduce the negative charge of DNA and to partially condense its normally large hydrodynamic volume and the ability to escape from lysosomes.…”
Section: Discussionmentioning
confidence: 99%
“…3 In our previous studies, an oligodeoxynucleotide (ODN) that was designed based on human mitochondrial DNA (MT01), was demonstrated to promote the proliferation and activation of osteoblasts and stimulate the proliferation and differentiation of bone marrow mesenchymal stem cells (BMSCs) into osteoblasts. [4][5][6][7] However, crucial problems such as poor oligonucleotide stability in the presence of nuclease activity in vitro and in vivo, and low intracellular penetration, would limit its wide application to enhance osteogenic capacity. 8 To overcome these problems, chemical modications of ODNs have been employed, mainly focusing on the phosphodiester backbone and/or the sugar moiety.…”
Section: Introductionmentioning
confidence: 99%
“…By their multipotency, BMMSCs hold great promise for clinical applications of achieving tissue regeneration. Recent studies have shown that they contribute to formation of all periodontal tissues, including periodontal ligament, cementum, and alveolar bone, thus might be an alternative cell source to achieve periodontal regeneration . However, precise mechanisms underlying these effects had remained poorly understood, which limited advanced application of BMMSCs for treating periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…Actived TLR9 on osteoblast's surface initiates extracellular signal-regulated protein kinase and P38 to release tumor necrosis factor α, then enhancing the expression of macrophage colony-stimulating factor to regulate osteoclasts [11]. The CpG ODN yet plays a positive role in osteogenic differentiaion of bone mesenchymal stem cells [12] and pre-osteoblasts [13].…”
Section: Introductionmentioning
confidence: 99%